1987
DOI: 10.2165/00003088-198713050-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics of Lignocaine and β-Adrenoceptor Antagonists in Patients with Acute Myocardial Infarction

Abstract: Lignocaine (lidocaine) and beta-adrenoceptor antagonists are widely used after acute myocardial infarction. The therapeutic value of these agents depends on the achievement and maintenance of safe and effective plasma concentrations. Lignocaine pharmacokinetics after acute myocardial infarction (MI) are controlled by a number of variables. The single most important is left ventricular function, which affects both volume of distribution and plasma clearance. Other major factors include bodyweight, age, hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 157 publications
2
4
0
Order By: Relevance
“…Fraction bound values obtained using the 96‐well dialysis block and the Spectrum apparatus were very similar to each other and consistent with literature values21–30(Table 1). There were minor shifts in fraction bound values between successive experiments that were attributed to intersubject variations in plasma protein concentrations 31–34.…”
Section: Resultssupporting
confidence: 89%
“…Fraction bound values obtained using the 96‐well dialysis block and the Spectrum apparatus were very similar to each other and consistent with literature values21–30(Table 1). There were minor shifts in fraction bound values between successive experiments that were attributed to intersubject variations in plasma protein concentrations 31–34.…”
Section: Resultssupporting
confidence: 89%
“…In lidocain-challenged animals, it was hypothesizes after examining the effects of blocking action potential of the olfactory nerve (ON). The apparent stimulation and subsequent depression produced by applying local anesthetics to the CNS presumably were reported due to suppression of neuronal activity (Nattel et al, 1987;Brunton et al, 2008). The nerve blocking effects impaired the conduction of action potential in the olfactory nerve leading to the suppression of neuronal function (Stakic et al, 2011 suggested that to prevent systemic exposure, an immediate absorption is always required through intranasal route.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In a subgroup of four patients who had a pharmacokinetic profile similar to an intravascular injection, the true peak concentrations were unknown because the first plasma levels obtained at five minutes were already falling. It was difficult for us to obtain reliable blood samples earlier because the study design required a slow and progressive (over two minutes) injection of lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of lidocaine in this study was motivated essentially by its short half-life, 14 in agreement with the duration of the procedure, and its low intrinsic toxicity compared with other amide local anesthetics. We compared IL anesthesia with iv analgesia associating NP.…”
Section: Discussionmentioning
confidence: 99%